Electrical transportation mechanisms of molybdenum disulfide flakes-graphene quantum dots heterostructure embedded in polyvinylidene fluoride polymer - Ooi, Poh Choon; Mohammad Haniff, Muhammad Aniq Shazni; Mohd Razip Wee, M.F.; Goh, Boon Tong; Dee, Chang Fu; Mohamed, Mohd Ambri; Majlis, Burhanuddin Yeop (Nature Research, 2019)
In the interest of the trend towards miniaturization of electronic gadgets, this study demonstrates a high-density data storage device with a very simple three-stacking layer consisting of only one charge trapping layer. A simple solution-processed technique has been used to fabricate the tristable non-volatile memory. The three-stacking layer was constructed in between two metals to form a two-terminal metal-insulator-metal structure. The fabricated device showed a large multilevel memory hysteresis window with a measured ON/OFF current ratio of 10 7 that might be attributed to the high charge trapped in molybdenum disulphide (MoS 2 ) flakes-graphene quantum dots (GQDs) heterostructure. Transmission electron microscopy was performed to examine the orientation of MoS 2 -GQD and mixture dispersion preparation method. The obtained electrical data was used further to speculate the possible transport mechanisms through the fabricated device by a curve fitting technique. Also, endurance cycle and retention tests were performed at room temperature to investigate the stability of the device. © 2019, The Author(s).